Pemetaan Risiko Kerentanan Wilayah Terhadap Banjir Di PesisirTeluk Kendari Provinsi Sulawesi Tenggara - Bahir, Nitrawati; Yunus, Lukman; Sawaludin, Sawaludin (Universitas Halu Oleo, 2017)
Risk Mapping Vulnerability towards Flooding at the Gulf Coast Kendari, Southeast Sulawesi Province. Thesis, Kendari: Faculty of Earth Science and Technology, Halu Oleo University, July 2016.The study area in this study includes the entire Gulf coast of Kendari which consist of six sub-districts and 45 villages. The technique of collecting data is through the data used is the method ofGeographical Information Systems (GIS) towards skoring, weighting and overlay each parameter. The parameters that used are elevation, land use, soils, rivers, rainfall, spatial pattern an conditions of the shoreline.The result of this study is: (I) the very low risk is at an altitude of 51-100 masl for the district of Poasia and Abeli, in the district of Poasia also contained the risk level at a height of 0-25 masl which also scattered in the district of Kambu. From the district Mandonga, West Kendari and the District of Kendari, spead at an altitude of51 to more than 400 masl. (II) The low risk is at an altitude of 26-51 masl Mandonga at a height of 0-26 masl, West Kendari and contained at an altitude of 51-100 masl. The higher risk (III) are distributed unevenly across the district and be at the certain height in each district. 0-50 masl and contained in all districts with a scale which not widely. (IV) A very high of vulnerabilities is at an altitude of 0-25 masl at the entire coastal region of the location of research.Keywords: Risk, Vulnerability, Flood, bay GISDOI :Â 10.5281/zenodo.2658186